2020
DOI: 10.1134/s2079970520030156
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Spatial Dynamics and Diffusion Factors across Russian Regions

Abstract: The observed spread of coronavirus infection across Russian regions, as a first approximation, obeys the classic laws of diffusion of innovations. The article describes in detail theoretical approaches to the analysis of the spread of social diseases and discusses methodological limitations that reduce the possibility of predicting such phenomena and affect decision-making by the authorities. At the same time, we believe that for most regions, including Moscow, until May 12, 2020, the dynamics of confirmed cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 19 publications
3
17
0
1
Order By: Relevance
“…For these settlements the impact of the COVID-19 pandemic on public life can be assessed by means of Yandex self-isolation index [Zemtsov, Baburin, 2020] in the period before the self-isolation and during two weeks after it. «Self-isolation index is an integrated indicator, which is computed according to the data on using the various Yandex 's applications and services.…”
Section: Seismic Data and Methodsmentioning
confidence: 99%
“…For these settlements the impact of the COVID-19 pandemic on public life can be assessed by means of Yandex self-isolation index [Zemtsov, Baburin, 2020] in the period before the self-isolation and during two weeks after it. «Self-isolation index is an integrated indicator, which is computed according to the data on using the various Yandex 's applications and services.…”
Section: Seismic Data and Methodsmentioning
confidence: 99%
“…Hence, there is a need to determine the exact location of the point (knots) where the series structure is changed. The detailed discussion to select the location of knots is discussed in Denison ( 1998 ), Biller ( 2000 ), and Ülker and Arslan ( 2009 ). Recently, this model is discussed by Kumar et al ( 2020 ) for testing the unit root hypothesis in the presence of spline function through posterior odds ratio and applied in monthly import series of ASEAN Regional Forum (ARF) countries.…”
Section: Model Specificationmentioning
confidence: 99%
“…Later, when investigating the meteorological controls on the spread of SARS-CoV-2 in Russia using correlation analysis and factor analysis, Shankar et al (2021) indicated that the increase of temperature increases the spreading and the decreased humidity with increase death rates. Spatial dynamics and diffusion factors across Russian regions were analyzed in a study by Zemtsov and Baburin (2020). In that study, Zemtsov and Baburin (2020) have revealed that the SARS-CoV-2 has spread faster in regions where the population has a higher susceptibility to diseases.…”
Section: Identification Of Correlations Between Covid-19 and Natural Socio-economic Factorsmentioning
confidence: 99%